2020
DOI: 10.1111/ddi.13180
|View full text |Cite
|
Sign up to set email alerts
|

Geographical patterns in phylogenetic diversity of Chinese woody plants and its application for conservation planning

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 124 publications
2
14
0
Order By: Relevance
“…In agreement with the pattern of vascular plants on the QTP reported by Yan et al [28], and given our investigation sites were located on the northwest to the southeast part of the plateau as well as at high-latitude, we found that the mean of species richness was only approximately ten. Besides, we observed a strong correlation between species richness (SR) and phylogenetic diversity (Faith's PD), which is consistent with previous studies on woody plants in China [48], vascular plants in dry sandy heathlands [49], and shrubs in Mediterranean-type regions [50]. This congruency might be the product of evolution and ecological processes-the highly symmetrical phylogenies, lower species richness and high spatial autocorrelation all result in the strong SR-PD correlation [51].…”
Section: Discussionsupporting
confidence: 90%
“…In agreement with the pattern of vascular plants on the QTP reported by Yan et al [28], and given our investigation sites were located on the northwest to the southeast part of the plateau as well as at high-latitude, we found that the mean of species richness was only approximately ten. Besides, we observed a strong correlation between species richness (SR) and phylogenetic diversity (Faith's PD), which is consistent with previous studies on woody plants in China [48], vascular plants in dry sandy heathlands [49], and shrubs in Mediterranean-type regions [50]. This congruency might be the product of evolution and ecological processes-the highly symmetrical phylogenies, lower species richness and high spatial autocorrelation all result in the strong SR-PD correlation [51].…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, conservation actions for tropical and subtropical floras are urgently needed to halt biodiversity loss under future warming. However, the existing protected areas (PA) in southern China are sporadic and the coverage of these PAs is only about half of the average level in China (Xu et al 2017, Cai et al 2021. Therefore, our study calls for the establishment of more PAs or expansion of the existing PAs in southern China, especially in the Yunnan-Guizhou Plateau and the Nanling Mountains.…”
Section: Discussionmentioning
confidence: 95%
“…We suggest that the dynamics of HNIs should be monitored and evaluated regularly. Besides, to achieve a more comprehensive understanding, it is also suitable and needed to evaluate the HNIs from other profiles, such as different taxa and levels of biodiversity or conservation status (Cai et al, 2020; Su et al, 2021).…”
Section: Discussionmentioning
confidence: 99%